Quality of dry fish from markets in Andhra Pradesh - Panduranga Rao, C.C., Basu, S., Khasim, D.I., Gupta, S.S. and (Fishery Technology, 2021)
Dry fish samples were procured from different fish markets and subjected to biochemical and bacteriological evaluation for assessing quality. The quality of market samples was compared with the samples dried in laboratory and in the mechanical drier [sic]. Most of the market samples had high moisture and sand contents. TVN values of market samples were high showing poor quality of the finished product.